2022
DOI: 10.1136/bmjopen-2021-058704
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and the risk of HIV acquisition: findings from population-based surveys in six sub-Saharan African countries (2016–2017)

Abstract: ObjectiveTo assess the potential bidirectional relationship between food insecurity and HIV infection in sub-Saharan Africa.DesignNationally representative HIV impact assessment household-based surveys.SettingZambia, Eswatini, Lesotho, Uganda and Tanzania and Namibia.Participants112 955 survey participants aged 15–59 years with HIV and recency test results.MeasuresRecent HIV infection (within 6 months) classified using the HIV-1 limited antigen avidity assay, in participants with an unsuppressed viral load (&g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…48,49 One study conducted using PHIA data found that food assistance receipt decreased the risk of both transactional sex and HIV infection in a pooled sample from African countries. 50 We found, however, that household food insecurity is not a significant confounder in the relationship between mobility and transactional sex, contrary to the intrinsic risk pathway posited by Cassels and colleagues. 23 It also does not exacerbate the association between mobility and transactional sex as an effect modifier.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…48,49 One study conducted using PHIA data found that food assistance receipt decreased the risk of both transactional sex and HIV infection in a pooled sample from African countries. 50 We found, however, that household food insecurity is not a significant confounder in the relationship between mobility and transactional sex, contrary to the intrinsic risk pathway posited by Cassels and colleagues. 23 It also does not exacerbate the association between mobility and transactional sex as an effect modifier.…”
Section: Discussioncontrasting
confidence: 95%
“…48,49 One study conducted using PHIA data found that food assistance receipt decreased the risk of both transactional sex and HIV infection in a pooled sample from African countries. 50…”
Section: Discussionmentioning
confidence: 99%
“…Our risk factor analysis also found an association, among AGYW, between no food in the house in the past four weeks and ever STI-testing; similarly, there was evidence that AGYW residing in households with relatively less wealth were more likely to have ever STI tested. In population-based surveys conducted in six African countries, severe food insecurity, defined as having no food in the house more than three-times in the past month, was associated with an increased risk of HIV infection [ 37 ]. This increased risk was due, in part, to increased reliance on selling sex [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A household wealth quintile was generated using principal components analysis of assets [26]. Occurrence and frequency of food insecurity was assessed in the last 4 weeks with food insufficiency defined as no food in the house 3 times or more [27]. Educational attainment was based on the highest level attended.…”
Section: Methodsmentioning
confidence: 99%